Comprehensive Analysis of mRNA and lncRNA Transcriptomes Reveals the Differentially Hypoxic Response of Preadipocytes During Adipogenesis - Zhang, Jinwei; Ma, Jideng; Zhou, Xiankun; Hu, Silu; Ge, Liangpeng; Sun, Jing; Li, Penghao; Long, Keren; Jin, Long; Tang, Qianzi; Liu, Lingyan; Li, Xuewei; et al. (Frontiers in Genetics, 2020)
Local hypoxia has recently been reported to occur in the white adipose tissue (WAT) microenvironment during obesity. Adipocytes have a unique life cycle that reflects the different stages of adipogenesis in the WAT niche. Long noncoding RNAs (lncRNAs) play an important role in the cellular response to hypoxia. However, the differentially hypoxic responses of preadipocytes during adipogenesis and the potential role of lncRNAs in this process remain to be elucidated. Here, we evaluated the differentially hypoxic responses of primary hamster preadipocytes during adipogenesis and analyzed mRNA and lncRNA expression in same Ribo-Zero RNA-seq libraries. Hypoxia induced HIF-1α protein during adipogenesis and caused divergent changes of cell phenotypes. A total of 10,318 mRNAs were identified to be expressed in twenty libraries (five timepoints), and 3,198 differentially expressed mRNAs (DE mRNAs) were detected at five timepoints (hypoxia vs normoxia). Functional enrichment analysis revealed the shared and specific hypoxia response pathways in the different stages of adipogenesis. Hypoxia differentially modulated the expression profile of adipose-associated genes, including adipokines, lipogenesis, lipolysis, hyperplasia, hypertrophy, inflammatory, and extracellular matrix. We also identified 4,296 lncRNAs that were expressed substantially and detected 1,431 DE lncRNAs at five timepoints. Two, 3, 5, 13, and 50 DE mRNAs at D0, D1, D3, D7, and D11, respectively, were highly correlated and locus-nearby DE lncRNAs and mainly involved in the cell cycle, vesicle-mediated transport, and mitochondrion organization. We identified 28 one-to-one lncRNA-mRNA pairs that might be closely related to adipocyte functions, such as ENSCGRT00015041780-Hilpda, TU2105-Cdsn, and TU17588-Ltbp3. These lncRNAs may represent the crucial regulation axis in the cellular response to hypoxia during adipogenesis. This study dissected the effects of hypoxia in the cell during adipogenesis, uncovered novel regulators potentially associated with WAT function, and may provide a new viewpoint for interpretation and treatment of obesity.